BRINCADEIRA DE CRIANÇA: O pião como objeto pedagógico no processo de ensino-aprendizagem de física no terceiro ano do ensino médio. - BARROS, Thauany Barreto (2018)
The transmission of knowledge finds difficulties in the contextualization and assimilation of subjects by the students. Due to these issues, this work has as a goal to promote science in a entertaining way by using the toy, based in the social-constructive pedagogical methodology proposed by Lev Vigotsky. With this in mind, the Educational Product is organized in a script composed by a didactic sequence with experimental activities, by using the spinning top, aiming at a better understanding of the subjects related to rotational dynamics. We extend, as part of the subject of study, the demonstration of the "spinning top with electromagnetic transmission" experiment, which illustrates a continuum rotational motion, providing a more significant learning experience. The present work has been developed with the senior year students of Paralelo Private Highscool, located in São Luís - MA, during 2018.